Penggunaan Alat Peraga Cermin dalam Meningkatkan Hasil Belajar IPA Bagi Siswa Kelas V SD Negeri Maraeli Kecamatan Jailolo Selatan - Apridayani Marasabessy; Munir Latukau (Peneliti.net, 2022)
Basically, science learning aims to prepare students to be responsive to their environment, because by learning science students can learn to understand natural phenomena that occur in their environment. (Tias 2017). Based on the results of research at SD Negeri Maraeli is the lack of attention from teachers about the use of teaching aids that are used in learning, thus making student achievement or learning outcomes not increase, so far the method that is often used by teachers at SD Negeri Maraeli is only by memorizing and taking notes, which is not followed by a deep understanding or understanding, then as students do not connect what they learn with how it is used in real life. This research uses class action research, which is a research that was developed together to make improvements. Through the application by using teaching aids provided by the teacher, students can understand the concept of a mirror and its nature well. The results in this study are: Learning using teaching aids provides elementary school teachers with skills and insight to be able to create and innovate in the classroom so as to create a dynamic and fun atmosphere, and students' intellectual, social and emotional abilities can develop well. developed because it is very useful for the development of students as a whole. Learning with media can increase students' enthusiasm for learning